I Разложите на множители... 1) x⁴ - 25 y²; 2)4b² - 0.01c⁶; 3)8a³ + c³; 4) x⁹ - 27; 5)9ab² - 16ac²; 6)-20xy³ + 45x³y; II Упростите выражение... 1) √50x + √32x - √98x; 2)(√a + √2 )(√a - √2) - (√a - √2) * √a; 3)(√x + √y)² - ...
I Разложите на множители... 1) x⁴ - 25 y²; 2)4b² - 0.01c⁶; 3)8a³ + c³; 4) x⁹ - 27; 5)9ab² - 16ac²; 6)-20xy³ + 45x³y; II Упростите выражение... 1) √50x + √32x - √98x; 2)(√a + √2 )(√a - √2) - (√a - √2) * √a; 3)(√x + √y)² - (√x - √y)²; 4)(√x - √y)(x + √xy + y); Это все в одно номере! (
Ответ(ы) на вопрос:
Гость
1) x⁴ - 25 y²=(x²-5y)(x²+5y) 2)4b² - 0.01c⁶=(2b-0.1c³)(2b+0.1c³) 3)8a³ + c³=(2a+c)(4a²-2ac+c²) 4) x⁹ - 27=(x³)³ - 3³ = (x³-3)(x⁶+3x³+9) 5)9ab² - 16ac²=a(9b²-16c²)=a(3b-4c)(3b+4c) 6)-20xy³ + 45x³y=-5xy(4y²-9x²)+-5xy(2y-3x)(2y+3x) 1) √50x + √32x - √98x=5√2x+4√2x+9√2x=18√2x 2)(√a + √2 )(√a - √2) - (√a - √2) * √a=√a² - √2² - a + √(2a) = a-2-a+√(2a)=√(2a)-2 3)(√x + √y)² - (√x - √y)²=(√x+√y-√x+√y)(√x+√y+√x-√y)=2√y * 2√x = 4√(xy) 4)(√x - √y)(x + √xy + y)=√x³ - √y³
Не нашли ответ?
Похожие вопросы